IBN ABIDIN'S STUDENTS AND HIS PUBLISHED TREATISES (The Journal of Interdisciplinary Human Studies, 2026)
This article examines Ibn Abidin’s scholarly legacy through a comprehensive analysis of his students and published treatises. The study demonstrates that his scholarly influence continued through the activities of his students, while his juristic views were reflected in his treatises devoted to a wide range of themes. In addition, Ibn Abidin’s printed treatises are analyzed within the framework of worship, family issues, transactions, waqf, fatwa, judicial practice, custom, and economic relations. The article, based on relevant primary and secondary sources, explores his scholarly school, the practical orientation of his juristic thought, and his place within the Hanafi legal tradition.
Keywords: Ibn Abidin; Hanafi fiqh; scholarly legacy; students; treatises; fatwa; muftihood; waqf; custom; transactions; Damascus